Energy and Water Conservation in Biodiesel Purification Processes - Hastie, Michele (Université d'Ottawa / University of Ottawa, 2011)
Biodiesel purification processes generate wastewater streams that require a large amount of energy when distillation is used as a treatment technology. Process simulation software was used to show that an alternative water treatment process involving ion exchange would require only 31% of the energy used by distillation. Experiments showed that multiple washing stages were required to meet the standard specification for sodium, an impurity present in crude biodiesel, when washing biodiesel made from used frying oil. A comparison was made between washing biodiesel in a cross-current washing configuration and a counter-current configuration. Both configurations met the specification for sodium within three washing stages; however, the counter-current configuration required less water, making it the more efficient process. Lastly, the removal of sodium from wastewater samples using an ion exchange resin was experimentally investigated. The results validated the use of ion exchange to reduce energy consumption in biodiesel purification.
Keywords: biodiesel; purification; wastewater; ion exchange